2003
DOI: 10.1074/jbc.m302295200
|View full text |Cite
|
Sign up to set email alerts
|

Frameshifted β-Amyloid Precursor Protein (APP+1) Is a Secretory Protein, and the Level of APP+1 in Cerebrospinal Fluid Is Linked to Alzheimer Pathology

Abstract: Molecular misreading of the ␤-amyloid precursor protein (APP) gene generates mRNA with dinucleotide deletions in GAGAG motifs. The resulting truncated and partly frameshifted APP protein (APP ؉1 ) accumulates in the dystrophic neurites and the neurofibrillary tangles in the cortex and hippocampus of Alzheimer patients. In contrast, we show here that neuronal cells transfected with APP ؉1 proficiently secreted APP ؉1 . Because various secretory APP isoforms are present in cerebrospinal fluid (CSF), this study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…2d, lanes 3 and 6) could be detected in the culture medium. These results are in agreement with our recent publication in which we show that APP +1 is present in the culture medium of transfected neuronal SH-SY5Y cells and in human cerebral spinal fluid (CSF) (Hol et al 2003). Therefore, it can be concluded that also in non-neuronal HEK293 cells APP +1 is a secretory protein.…”
Section: Subcellular Localisation Of App +1 and App 695supporting
confidence: 82%
See 3 more Smart Citations
“…2d, lanes 3 and 6) could be detected in the culture medium. These results are in agreement with our recent publication in which we show that APP +1 is present in the culture medium of transfected neuronal SH-SY5Y cells and in human cerebral spinal fluid (CSF) (Hol et al 2003). Therefore, it can be concluded that also in non-neuronal HEK293 cells APP +1 is a secretory protein.…”
Section: Subcellular Localisation Of App +1 and App 695supporting
confidence: 82%
“…To exclude any cell type specific effects, transfection experiments were repeated on human neuronal cell-lines, i.e. SH-SY5Y (Hol et al 2003), SK-N-SH and CHP-100, which gave similar results (data not shown). From these experiments we concluded that APP 695 and APP +1 are highly expressed from our constructs in HEK293 cells.…”
Section: Subcellular Localisation Of App +1 and App 695mentioning
confidence: 65%
See 2 more Smart Citations
“…APP +1 accumulates in the neurofibrillary tangles and neuropil threads of AD and Down syndrome patients [4] . In cerebrospinal fluid, APP +1 correlated negatively with increasing Braak stages [20] . This means that APP +1 is an additional biomarker for the early diagnosis of AD.…”
Section: +1mentioning
confidence: 99%